Design, Synthesis, Characterizations, and Processing of a Novel c-Donor-nc-Bridge-cf-Acceptor Type Block Copolymer for Optoelecronic Applications - H. Nguyen, Thuong; Hasib, Muhammad; Wang, Dan; Sun, Sam-Shajing (Journal of Research Updates in Polymer Science, 2016)
A novel c-D-nc-B-cf-A (or DBfA) type of block copolymer has been designed, synthesized, characterized, and preliminarily studied for optoectronic applications, where c-D is a conjugated donor type polyphenylenevinylene (PPV) block, nc-B is a non-conjugated bridge unit, and cf-A is a conjugated and fluorinated acceptor type PPV block. The frontier HOMO/LUMO orbital levels of D and fA conjugated blocks are -5.22/-3.06 and -6.10/-3.43 as determined from electrochemical and optical measurements. Photoluminescence emissions of D and fA are quenched in DBfA indicating a potential photo induced charge separation pathway between the donor and the acceptor blocks. Solid state thin film studies revealed more uniform and nano-scale phase separated morphologies in DBfA as compared to D/fA blend. A two orders of magnitude enhancement of photoelectric energy conversion efficiency was observed in a best solar cell fabricated from the DBfA block copolymer as compared to a best cell fabricated from the corresponding D/fA blend. Such significant photoelectric conversion enhancement could be attributed to the improvements of phase separated and bicontinously ordered nanostructure (BONS) morphology in DBfA as compared to D/fA.